1996
DOI: 10.1021/bi960292+
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of an Engineered Insulin Monomer at Neutral pH

Abstract: Insulin circulates in the bloodstream and binds to its specific cell-surface receptor as a 5808 Da monomeric species. However, studies of the monomer structure and dynamics in solution are severely limited by insulin self-association into dimers and higher oligomers. In the present work we use site-directed mutagenesis of the dimer- and hexamer-forming surfaces to yield the first insulin species amenable for structure determination at neutral pH by nuclear magnetic resonance (NMR) spectroscopy. The preferred i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
212
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(221 citation statements)
references
References 51 publications
9
212
0
Order By: Relevance
“…As a control, both isomers are stable in similar buffer without free thiol catalyst (data not shown). This disulfide rearrangement experiment further confirmed that these two isomers of [1][2][3][4][5][6][7][8][9]-PIP are thermodynamically controlled folding products with different disulfide linkages. If we compare the disulfide reshuffling process of isomers 1 and 2 at different time points, we can see that the conversion from isomer 1 into isomer 2 is faster than the reverse direction (data not shown).…”
Section: [1-9]pip Was Expressed In Yeast Assupporting
confidence: 52%
See 4 more Smart Citations
“…As a control, both isomers are stable in similar buffer without free thiol catalyst (data not shown). This disulfide rearrangement experiment further confirmed that these two isomers of [1][2][3][4][5][6][7][8][9]-PIP are thermodynamically controlled folding products with different disulfide linkages. If we compare the disulfide reshuffling process of isomers 1 and 2 at different time points, we can see that the conversion from isomer 1 into isomer 2 is faster than the reverse direction (data not shown).…”
Section: [1-9]pip Was Expressed In Yeast Assupporting
confidence: 52%
“…The expression plasmids encoding Expression, Purification, and Identification of [1][2][3][4][5][6][7][8][9]PIP, [1][2][3][4]PIP, [1][2][3][4][5][6][7][8][9][10]Mini-IGF-1, and [1][2][3][4][5]…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations